Responses of Parasitic Nematodes to Volatile Organic Compounds Emitted by Brassica nigra Roots - Žiga Laznik; Tímea Tóth; Szabolcs Ádám; Stanislav Trdan; Ivana Majić; Tamás Lakatos (Agronomy)
Parasitic nematodes, particularly those in the Rhabditidae family, are vital components of belowground ecosystems, contributing to pest regulation and sustainable agriculture. This study investigated the chemotactic responses of three nematode species—Phasmarhabditis papillosa, Oscheius myriophilus, and O. onirici—to volatile organic compounds (VOCs) emitted by Brassica nigra roots under herbivory by Delia radicum larvae. Using a chemotaxis assay, the effects of five VOCs (dimethyl sulfide, dimethyl disulfide, allyl isothiocyanate, phenylethyl isothiocyanate, and benzonitrile) were tested at two concentrations (pure and 0.03 ppm) and two temperatures (18 °C and 22 °C). The results revealed that VOCs and temperature significantly influenced nematode responses, while nematode species and VOC concentration showed limited effects. Benzonitrile consistently demonstrated strong chemoattractant properties, particularly for O. myriophilus and O. onirici. Conversely, allyl isothiocyanate exhibited potent nematicidal effects, inhibiting motility and causing mortality. Dimethyl disulfide and dimethyl sulfide elicited moderate to strong attractant responses, with species- and temperature-dependent variations. Significant interactions between VOCs, temperature, and nematode species highlighted the complexity of these ecological interactions. These findings emphasize the ecological roles of VOCs in mediating nematode behavior and their potential applications in sustainable pest management. Benzonitrile emerged as a promising candidate for nematode-based biocontrol strategies, while allyl isothiocyanate showed potential as a direct nematicidal agent. The study underscores the importance of integrating chemical cues into pest management systems to enhance agricultural sustainability and reduce reliance on chemical pesticides.